Barriers to and acceptability of provider-initiated HIV testing and counselling and adopting HIV prevention behaviours in rural Uganda: A qualitative study - Kiene, Susan M.; Sileo, Katelyn; Wanyenze, Rhoda K.; Lule, Haruna; Bateganya, Moses H.; Jasperse, Joseph; Nantaba, Harriet (Journal of health psychology, 2015)
In Uganda, a nation-wide scale-up of provider initiated HIV testing and counseling (PITC) presents an opportunity to deliver HIV prevention services to large numbers of people. In a rural Ugandan hospital, focus group discussions and key informant interviews were conducted with outpatients receiving PITC and staff to explore the HIV prevention information, motivation, and behavioral skills strengths and weaknesses, and community and structural-level barriers to PITC acceptability and HIV prevention among this population. Strengths and weakness occurred at all levels, and results suggest brief client-centered interventions during PITC may be an effective approach to increase prevention behaviours in outpatient settings.
Keywords: AIDS; HIV; Prevention; Screening; Health Behaviour